Hubungan Layanan Bimbingan Konseling Dan Kemandirian Dengan Pengambilan Keputusan Karier Siswa - Jumeri Pamungkas, Achmad, Dr. Nanik Prihartanti, M.Si (2016)
This study aims to determine the relationship counseling service and the independence of the decision-making career. The hypothesis being tested is no relationship between counseling services and the independence of the decision-making career. This type of research is a quantitative correlation with data collection technique using a scale. The sampling technique of population studies. The research location in the Junior Pati. The data collection is done by three scales, namely counseling services, self-reliance, and decision-making career. Based on the analysis of data using multiple regression analysis result that there was a significant relationship between counseling services and the independence of the decision-making career. Effective contribution counseling services and career decision-making independence by 51,8 %. The results also found a correlation between the value of guidance and counseling services with career decision-making showed a value of rx1y amounted to 0,642 with the effective contribution of 33,28 %. The value of the correlation between the independence of the decision-making career showed a value of rx2y amounted to 0,685 with the effective contribution of 18,52 %. The results showed there was a highly significant relationship between counseling services and the independence of the decision-making career. The conclusion of the service relationship counseling and independence are positive on career decision making.